Peran Ekonomi Perkotaan dalam Ekonomi Nasional - Simarmata, Djamester A. (UI Scholars Hub, 2002)
This article discusses the indirect roles of urban economy to the national economy through its property and land market. Some national economic instruments have inevitable effects on the local variables, making the concept of regional autonomy limited. The level of interest rates is determined by the central bank, which has a strong nation wide effects, influencing the valuation of property and land, namely in the urbanized areas. One of the main concerns of many people and both local and national governments in the urbanized area is on housing. How should the national policies and local policies be harmonized so that the lower households could afford decent shelters for their families? And how should the policies on the property sectors with its interrelation to the banking system be remedied in order to avoid its negative impacts to the national economy. As is well known, the land and property sector largely depend on local policies.